Obesity and left ventricular mass in children - Mauliza Mauliza; Muhammad Ali; Melda Deliana; Tina Christina L Tobing (Indonesian Pediatric Society, 2015)
Background Obesity has negative effects on cardiac function during growth leading to increased heart size and mass, as a result of higher stroke volume and cardiac output.Objective To assess for a relationship between obesity and left ventricular mass (LVM) in children, as well as to assess for a correlation between the duration of obesity and LVM.Methods This cross-sectional study was conducted from October 2011 until February 2012 in Medan and included 30 obese and 30 normal weight children, aged 6 to 13 years. All subjects underwent complete echocardiography examinations to assess LVM and other left ventricular parameters. The Devereux formula was used to measure LVM.Results During the study, 65 children underwent echocardiography, but 5 were subsequently excluded. The left ventricular dimensions in the obese group were significantly higher compared to normal weight group with regards to interventricular septum at end diastole (IVSd), interventricular septum at end systole (IVSS), left ventricular internal diameter at end diastole (LVIDd), left ventricular internal diameter at end systole (LVIDs), left ventricular posterior wall thickness at end diastole (LVPWd), left ventricular mass (LVM), and left ventricular mass index (LVMI) (P=0.0001). Duration of obesity and LVM had a moderate, positive correlation (r=0.407).Conclusion There is significantly higher LVM in the obese group than in the normal weight group. The duration of obesity had a moderate, positive correlation to LVM.